Muhtasib, Ombudsman and Malaysian financial Ombudsman scheme: A comparative study - Ilias, Ibtisam @ Ilyana; Hassan, Rusni; Ibrahim, Uzaimah (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
The growth of alternative dispute resolution (ADR) is an inevitable phenomenon due to inherent drawback of the conventional litigation. One of the most acceptable forms of ADR is ombudsman which is known as Muhtasibfrom Islamic perspective. In Malaysia, the first ombudsman institution has been established in financial industry operated by the Ombudsman for Financial Services (OFS). It is one of the moves initiated by Bank Negara Malaysia (BNM) with a view of providing simple, inexpensive and effective redress mechanism to financial consumers. Applying doctrinal research methodology, this paper examines the background of Muhtasib and ombudsman as well as their functions and characteristics. Similar observation is made vis-à-vis the OFS. These three aspects are subsequently compared to investigate the similarities and differences between the Muhtasib, ombudsman and the OFS. The study concludes that both the Muhtasib and ombudsman have undergone evolution from their original structure. Despite derived from different origin and with a different terminology used, it is resolved that in the contemporary milieu of alternative dispute resolution, the function of Muhtasib and ombudsman is ultimately to settle the dispute amicably, impartially, effectively and independently. The key principles of ombudsman are also in line with Shariah principles and have been incorporated in the establishment of the OFS. Recommendation is made concerning the imposition of specific requirements on the ombudsmen of the OFS. This study provides a significant insight on the traditional and modern aspect of Muhtasib and ombudsman as well as the newly set up Malaysian OFS.